Answer:
6 years
Explanation:
The height of tree A can be modeled by ...
A = 36 +22y . . . . . where y is the number of years, height is inches
The height of tree B can be modeled by ...
B = 48 +20y . . . . . same deal
The two heights are the same when ...
A = B
36 +22y = 48 +20y
2y = 12 . . . . . . subtract 36+20y
y = 12/2 = 6
It will take 6 years for the trees to be the same height.
__
Note that you can "cut to the chase" by recognizing that the taller tree is growing at the slower rate, so the 12-inch difference in height is being reduced by 2 inches per year. (That is the meaning of 2y=12, above.) From there, it is a simple step to get to the answer: divide 12 by 2.